Response of A European Corn Borer, Ostrinia nubilalis, Population to Selection with An Ecdysone Agonist, Tebufenozide - Y. Andi Trisyono (Jurnal Perlindungan Tanaman Indonesia, 2000)
Response of a population of the European corn borer, Ostrinia nubilalis (Hubner), to selection with an ecdysone agonist, tebufenozide (RH-5992), was investigated. The selection was carried out by exposing newly hatched larvae of O. nubilalis on an artificial diet containing 0.285 ppm tebufenozide for four days. Throughout seven generations of selection, a slight decrease in the larval mortality, an increase in the pupal mortality, and a decrease in the number of offspring produced per female were noticed. After four generations of selection, a shift in susceptibility of the selected O. nubilalis larvae to tebufenozide was not observed. The acute and chronic effects of tebufenozide caused the loss of O. nubilalis population after seven generations of selection.